Association of dialysate calcium concentration with fetuin a level and carotid intima-media thickness in peritoneal dialysis patients. (February 2014) - Liang, Jianbo; Wang, Zebin; Liu, Guohui; Zhan, Junlin; Jiang, Liping; Jiang, Zongpei
Abstract Serum fetuin A has been shown to be associated with the risk of vascular calcification and atherosclerosis, and it can predict the onset of cardiovascular mortality in dialysis patients. The carotid intima-media thickness (cIMT) is an accessible and reliable method to identify the subclinical atherosclerosis. The aim of this study was to investigate the relationships between dialysate calcium concentrations and fetuin A or cIMT in patients undergoing peritoneal dialysis (PD). Forty patients, newly diagnosed end-stage renal disease (ESRD) and undergoing peritoneal dialysis, were enrolled in the study, with a calcium content of the peritoneal dialysis (PD) solution of 1.25 mmol/L in 20 patients (low-Ca group) and 1.75 mmol/L in 20 patients (standard-Ca group). The patients were followed up for 12 months after the PD conducted. Serum fetuin A was determined using a human fetuin A enzyme-linked immunosorbent assay kit and cIMT was detected using ultrasonic wave. We observed no difference between two groups with regard to the baseline data of fetuin A, cIMT, calcium, phosphorus, calcium-phosphorus product, high sensitivity CRP (hsCRP), parathyroid hormone (PTH), or lipid parameters. After 12 months follow-up, fetuin A (263.92 ± 16.1 vs. 282.76 ± 21.0, p = 0.017) and calcium-phosphorus product (39.85 ± 7.76 vs. 47.50 ± 6.65, p = 0.009) were obviously lower in the low-Ca group than standard-Ca group, the other serum parameters were not different between these two groups. Compared with baseline data, serum fetuin A concentration significantly reduced in low-Ca group ( p < 0.05). The number of patients with increased cIMT and newly occurring cardiovascular events in the low-Ca group were significantly reduced than standard-Ca group ( p < 0.05). In conclusion, our data suggest that low calcium dialysate treatment is associated with the decreased serum fetuin A concentration and serum calcium-phosphorus product, and it is associated with the reduced number of PD patients with increased cIMT or with newly occurring cardiovascular events. However, more studies with lager sample size should be performed in the future.